Biohybrids: Textile fibres provide scaffolds and highways for microbial translocation - Sherry, Angela; Dell’Agnese, Bruna Martins; Scott, Jane (Frontiers in Bioengineering and Biotechnology, 2023)
A cross-disciplinary approach, operating at the intersection of creative practice and scientific research, incorporated textile technology and microbiology to demonstrate textile fibres providing microbial scaffolds and highways during this study. The study evolved from previous research which showed bacteria utilising the water layer surrounding fungal mycelium for motility, termed the ‘fungal highway’, which led to the investigation of the directional dispersal of microbes across a range of fibre types. At a cellular scale, confocal microscopy provided evidence to show that bacteria were able to utilise a water layer surrounding the fibres, supporting the hypothesis that fibres can aid bacterial translocation through their use as ‘fibre highways’. Pseudomonas putida was shown to translocate around a liquid layer surrounding polyester, nylon, and linen fibres, yet no evidence of translocation was apparent on silk or wool fibres, suggesting microbes elicit different responses to specific fibre types. The application of the study centred around the use of biohybrids as a biotechnology to improve oil bioremediation by seeding hydrocarbon-degrading microbes into polluted environments via fibre highways. Findings showed that translocation activity around fungal highways did not diminish in the presence of crude oil, known to contain an abundance of toxic compounds, in comparison to oil-free controls. From a design perspective, textiles have huge potential to act as a conduit for water and nutrients, essential to sustain microorganisms within living materials. Using the moisture absorption properties of natural fibres, this research explored how to engineer liquid absorption rates using cellulosics and wool to produce shape-changing knitted fabrics suitable for adaptation to oil spills. A design series demonstrated the growth of fungal mycelium through knitted structures, highlighting the ability for natural fabrics to provide a scaffold to support microbial communities whilst retaining environmentally responsive shape-change. A final prototype demonstrated the potential to scale up the responsive capacities of the material system using locally produced UK wool. It conceptualised the uptake of a hydrocarbon pollutant by fibres and translocation of microbes along a fibre highway. The research works towards facilitating the translation of fundamental science and design into biotechnological solutions that can be used in real world applications.